If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -1(6 + -2y) = 8(y + -2) Y + (6 * -1 + -2y * -1) = 8(y + -2) Y + (-6 + 2y) = 8(y + -2) Reorder the terms: -6 + Y + 2y = 8(y + -2) Reorder the terms: -6 + Y + 2y = 8(-2 + y) -6 + Y + 2y = (-2 * 8 + y * 8) -6 + Y + 2y = (-16 + 8y) Solving -6 + Y + 2y = -16 + 8y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + Y + 6 + 2y = -16 + 6 + 8y Reorder the terms: -6 + 6 + Y + 2y = -16 + 6 + 8y Combine like terms: -6 + 6 = 0 0 + Y + 2y = -16 + 6 + 8y Y + 2y = -16 + 6 + 8y Combine like terms: -16 + 6 = -10 Y + 2y = -10 + 8y Add '-2y' to each side of the equation. Y + 2y + -2y = -10 + 8y + -2y Combine like terms: 2y + -2y = 0 Y + 0 = -10 + 8y + -2y Y = -10 + 8y + -2y Combine like terms: 8y + -2y = 6y Y = -10 + 6y Simplifying Y = -10 + 6y
| 0=12x^2-80x+84 | | x+0.16x+0.05x=6000 | | 0=12x^2-88x+96 | | 16/3(3/2)n-1 | | f*u*c*k*y*o*u*s*t*a*l*k*e*r*s=9 | | x+0.16x=6000 | | -6-7(3x-17)=-54 | | x*x=100x | | ×/5-1=3 | | 5=-7u+3(u+3) | | x+1.91=8.53 | | =(3x-8)(5x+6) | | 4(6-7a)=17 | | -log(x)=8.28 | | v=(14-2x)(6-2x) | | t^2-40=-76 | | v=x(16-2x)(6-2x) | | 1/2x-3/4=1/4 | | 49j^2-9=0 | | 33+2d=6(8d-7) | | x+20=3x+2 | | 8+4m-2=8m+4-2 | | 4(1/64)^2/3 | | z^2+74=0 | | 2x+50=2x+70 | | 9(4+v)+33v=13v | | 50+30-10x=80+20-2x | | -5/(2(400-5p)^1/2)=1 | | g^2+50=0 | | 8(7k+3)= | | 13/30x=39 | | 2x^2+4ax+bx-2ab=0 |